The impact of conservation agriculture adoption on farmer welfare: a comparative assessment of Zambia and Zimbabwe - Mungatana, Eric D. (University of Pretoria, 2021)
Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2021.